TANTANGAN DALAM PENYELESAIAN GUGATAN SEDERHANA : TANTANGAN DALAM PENYELESAIAN GUGATAN SEDERHANA - agustini, shenti (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Indonesia is a state of law. This is due to the existence of a fundamental judicial power that adheres to the principles of the administration of judicial power. One of the principles is the principle of simple, fast and low cost. This is manifested in the settlement of a simple lawsuit. The purpose of this study is to analyze the challenges of settling a simple lawsuit. The research method used is normative juridical and uses juridical and theoretical foundations in analyzing this research. The theory used is the Theory of Legal Certainty by Gustav and Theory of Legal Systems by Lawrence. The results of the study, it was found that Indonesia has provided legal certainty in the settlement of simple lawsuits by stipulating this in PERMA Number 4 of 2019. However, its application still varies based on obstacles caused by legal culture.